Summer Season and Recommended Vitamin D Intake Support Adequate Vitamin D Status throughout Pregnancy in Healthy Canadian Women and Their Newborns. Issue 4 (16th November 2019) - Perreault, Maude; Atkinson, Stephanie A; Meyre, David; Fusch, Gerhard; Mottola, Michelle F; ,
ABSTRACT: Background: Vitamin D deficiency in pregnancy is reported as a prevalent public health problem. Objectives: We aimed to evaluate, in pregnant Canadian women, 1 ) vitamin D intake, 2 ) maternal and cord serum 25-hydroxycholecalciferol [25(OH)D] and maternal 1, 25-dihydroxycholecalciferol [1, 25(OH)2 D], and 3 ) factors associated with maternal serum 25(OH)D. Methods: Women ( n  = 187; mean prepregnancy BMI 24.4 kg/m 2, mean age 31 y) recruited to the Be Healthy in Pregnancy study provided fasting blood samples and nutrient intake at 12–17 (early) and 36–38 (late) weeks of gestation, and cord blood. Vitamin D intakes (Nutritionist Pro™) and serum 25(OH)D and 1, 25(OH)2 D concentrations (LC-tandem MS) were measured. Results: Vitamin D intake was comparable in early and late pregnancy [median (IQR) = 586 (459, 859) compared with 689 (544, 974) IU/d; P  = 0.83], with 71% consumed as supplements. Serum 25(OH)D was significantly higher in late pregnancy (mean ± SD: 103.1 ± 29.3 nmol/L) than in early pregnancy (82.5 ± 22.5 nmol/L; P < 0.001) and no vitamin D deficiency (<30 nmol/L) occurred. Serum 1, 25(OH)2 D concentrations were significantly higher in late pregnancy (101.1 ± 26.9 pmol/L) than in early pregnancy (82.2 ± 19.2 pmol/L, P < 0.001, n  = 84). Cord serum 25(OH)D concentrations averaged 55% of maternal concentrations. In adjusted multivariate analyses, maternal vitamin D status in early pregnancy was positively associated with summer season (est.β: 13.07; 95% CI: 5.46, 20.69; P < 0.001) and supplement intake (est.β: 0.01; 95% CI: 0.00, 0.01; P < 0.001); and in late pregnancy with summer season (est.β: 24.4; 95% CI: 15.6, 33.2; P < 0.001), nonmilk dairy intake (est.β: 0.17; 95% CI: 0.02, 0.32; P  = 0.029), and supplement intake (est.β: 0.01; 95% CI: 0.00, 0.01; P  = 0.04). Conclusions: Summer season and recommended vitamin D intakes supported adequate vitamin D status throughout pregnancy and in cord blood at >50 nmol/L in healthy Canadian pregnant women. This trial was registered at clinicaltrials.gov as NCT01693510.